Adjuvant Versus Early Salvage Radiation Therapy for Men at High Risk for Recurrence Following Radical Prostatectomy for Prostate Cancer and the Risk of Death. Issue 20 (10th July 2021) - Tilki, Derya; Chen, Ming-Hui; Wu, Jing; Huland, Hartwig; Graefen, Markus; Wiegel, Thomas; Böhmer, Dirk; Mohamad, Osama; Cowan, Janet E.; Feng, Felix Y.; Carroll, Peter R.; Trock, Bruce J.; et al.
Abstract : PURPOSE: Adjuvant compared with early salvage radiation therapy (sRT) following radical prostatectomy (RP) has not been shown to reduce progression-free survival in randomized controlled trials. However, these trials might have missed a benefit in men with adverse pathology at RP given that these men were under-represented and immortal time bias might have been present; herein, we investigate this possibility. METHODS: We evaluated the impact of adjuvant versus early sRT on all-cause mortality (ACM) risk in men with adverse pathology defined as positive pelvic lymph nodes (pN1) or pGleason score 8-10 prostate cancer (PC) and disease extending beyond the prostate (pT3/4). We used a treatment propensity score to minimize potential treatment selection bias when estimating the causal effect of adjuvant versus early sRT on ACM risk and a sensitivity analysis to assess the impact that varying definitions of adverse pathology had on ACM risk adjusting for age at RP, PC prognostic factors, site, and the time-dependent use of post-RP androgen deprivation therapy. RESULTS: After a median follow-up (interquartile range) of 8.16 (6.00-12.10) years, of the 26, 118 men in the study cohort, 2, 104 (8.06%) died, of which 539 (25.62%) were from PC. After excluding men with a persistent prostate-specific antigen, adjuvant compared with early sRT was associated with a significantly lower ACM risk among men with adverse pathology at RP when men with pN1 PC were excluded (0.33 [0.13-0.85]; P = .02) or included (0.66 [0.44-0.99]; P = .04). CONCLUSION: Adjuvant radiation therapy should be considered in men with pN1 or pGleason score 8 to 10 and pT3/4 PC given the possibility that a significant reduction in ACM risk exists.